2021
DOI: 10.46474/jds.927181
|View full text |Cite
|
Sign up to set email alerts
|

Re-considering the Architectural Design Studio after Pandemic: Tools, Problems, Potentials

Abstract: The Covid-19 outbreak has significantly influenced all disciplines from economics to politics, especially health, and forced every discipline to develop new strategies to adapt to this situation. For this reason, education has been suspended as of mid-March 2020 in our country; after the break, education methods have changed in a mandatory and rapid way and largely switched to distance education. This compulsory transformation has required the creation of new methods and approaches, especially for applied cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…Researchers preferred that the function of the model to be built is simple, commensurate with the amount of information and experiences of first-year students so that it does not become an obstacle to students' creativity in design. This agreed with what was indicated by a previous study that students who focused on the design of the models and its structure did not reach satisfactory results about its function, due to the lack of their knowledge and experience (Ozorhon' et al, 2016). The researchers believed that the participation of a group of students in a full-scale model by 1:1 contributes significantly to the development of many students' skills as well as creativity in design.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Researchers preferred that the function of the model to be built is simple, commensurate with the amount of information and experiences of first-year students so that it does not become an obstacle to students' creativity in design. This agreed with what was indicated by a previous study that students who focused on the design of the models and its structure did not reach satisfactory results about its function, due to the lack of their knowledge and experience (Ozorhon' et al, 2016). The researchers believed that the participation of a group of students in a full-scale model by 1:1 contributes significantly to the development of many students' skills as well as creativity in design.…”
Section: Discussionsupporting
confidence: 89%
“…Through previous studies, it was noted that it is very important to plan for the first design decisions in which new architectural students made their first experiences (Ozorhon' et al, 2016). Not to mention that the study by Sidawi (2013), which was conducted in the period from 2010-2013 to students of the CAP, had indicated that the design studio environment is slowly improving, while it must be radically strengthened to help students produce creative projects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study is warranted because participants' perceptions have had a strong impact on the discussion surrounding the architectural design studio, and knowledge of students' learning experiences in that setting is important since these experiences contribute to architectural student learning. Without understanding their experiences, it may be difficult to facilitate positive change in the architectural design studio environment (Ozorhon and Lekesiz, 2021). The COVID-19 pandemic which necessitates online teaching and learning further emphasises the need to understand how these kind of courses can be conducted using the ODL approach to enhance the teaching and learning experience in the studio.…”
Section: Problem Statementmentioning
confidence: 99%
“…Her kademeden öğrenci ve eğitimci çerçevesinde pandemi koşullarındaki eğitime dair algıya, kalitesine, sınırlıklarına, avantaj ve dezavantajlarına yönelik birçok çalışma yapılmıştır (Altun Ekiz, 2020;Başaran vd., 2020;Buluk ve Eşitti;Genç vd., 2021;Genç ve Köker, 2021;Genç ve Gümrükçüoğlu, 2020;Karadağ ve Yücel, 2020). Tasarım stüdyo derslerine yönelik yapılan çalışmalar da ise çevrimiçi tasarım stüdyolarının kullanımı ile ilgili tutumlarını incelemek ve kullanımlarının öğrenme sürecini nasıl iyileştirebileceğini tartışmak için öğrencilerin görüşlerine başvurulmuştur (Alnusairat vd., 2020;Ceylan vd., 2020;Özorhon & Lekesiz, 2021;Varma & Jafri, 2020). Fakat eğitim mekânlarının yeni normale uyarlanması ile ilgili çalışmalar sınırlı sayıdadır.…”
Section: Covid Dönemi̇ Ve Mi̇marlik Eği̇ti̇mi̇unclassified